Welche Politik führt zu besserer Bildung? - Friederike Hertweck (Wirtschaftsdienst, 2025)
– The education system is crucial for individual and social development and a country's competitiveness. Current studies show a decline in the quality of education and growing inequality. Challenges such as a shortages of skilled labour and high workloads for teachers, combined with inadequate educational transitions, are exacerbating the situation. The coalition government has introduced reforms, including the Good Childcare Act and the Digital Pact 2.0, but implementation remains difficult. Future measures must focus on innovation, AI integration and coherent educational transitions in order to promote equal opportunities and resilience.
Keywords: I20; I25; I26; 330; Bildungswesen; Bildungspolitik; Deutschland; Bildungswesen; Bildungspolitik; Deutschland